Considering the Effects of Upper Body, Lower Body, and Their Combination on Post-Activation Performance Enhancement of Bowling Velocity Among Amateur Cricket Players - Sarmah, Bhargav; Bordoloi, Nishanta; Narvariya, Pushpendra; Thapa, Rohit Kumar (Physical Education Theory and Methodology, 2025)
Objectives. This study aimed to investigate the effects of post-activation performance enhancement on bowling velocity among amateur cricket players using multiple interventions as conditioning activities focusing on the upper body, lower body, and a combination of both. Materials and methods. Eight amateur cricket bowlers were recruited for the study and, in a randomized crossover manner, allocated to conditioning activities aimed at the upper body (i.e., 10 pull-ups + 6 wall ball slams), lower body (i.e., 10 air squats + 6 broad jumps), or both (5 pull-ups + 3 wall ball slams combined with 5 air squats + 3 broad jumps). The bowling velocity was measured at baseline and after one minute and four minutes of completing the intervention. Results. The findings indicate no significant improvement (p = 0.939) in ball velocity compared to the control condition after the three experimental conditions. However, post-hoc results showed a substantial decrease in bowling velocity after one minute. Conclusions. In conclusion, conditioning activities using pull-ups and wall ball slams for the upper body, air squats, and broad jumps for the lower body, or their combination, do not induce post-activation performance enhancement during cricket bowling.